MemeWar 2 : game platform for artificial intelligence research - Teo, Joyce Mei Li (2014)
MemeWar is a free-to-download and play 3D multi-agent simulation game that allows user to train an agent to fight against others in a battle. It is also a platform for researchers to easily conduct artificial intelligence researches. This game has been in the market for a few years, but it has yet to gain its popularity in the gaming industry. Thus, to draw attention from the crowds, a revision of this game known as MemeWar 2 is implemented. Besides having most of the features in MemeWar, it has a brand new look and enhanced gameplay mechanics. It is intended to replace the existing MemeWar.